A comparative study of transport behaviour of monovalent (Li1+) and trivalent (Bi3+) doped La1-xLixMnO3+δ and La0.67-yBiyCa0.33MnO3 CMR materials. (28th July 2020) - Taran, S.; Yang, H. D.
ABSTRACT: A comparative study of the field-dependent resistivity (ρ) and thermoelectric-power (TEP) of Li-doped La1-x Lix MnO3+δ and Bi-doped La0.67-y Biy Ca0.3 MnO3 is made. The perovskite structure of the La1-x Lix MnO3+δ is rhombohedrally distorted in contrast to the La0.67-y Biy Ca0.3 MnO3 showing orthorhombic symmetry. The metallic part of resistivity of La1-x Lix MnO3+δ is best fitted with an expression ρ(T) = ρ0 + ρ4.5 T 4.5 + C/sinh 2 (hνs /2kB T) containing small-polaron contribution (last term), involving a relaxation time due to soft optical-phonon mode. This is in sharp contrast to the resistivity of La0.67-y Biy Ca0.3 MnO3 where, the ρ(T) data are best fitted with the electron-magnon scattering model ρ = ρO + ρT T 2.5 . These results suggest the optimum requirements for the formation of optical-polaron in manganites in the metallic phase, which depends on the characteristics of the constituent A-site ion (valence-state, ionic-radii, etc.) of manganites. Unlike Li-doping, the Bi-doping does not induce any hopping site indicated from the critical analysis of the TEP data.